Enzyme immobilization: what have we learned in the past five years?. (24th November 2021) - Almeida, Francisco L. C.; Prata, Ana S.; Forte, Marcus B. S.
Abstract: Immobilized enzymes have been widely applied in several fields over the past years, and the number of studies on the topic has been rapidly increasing. This review aimed to examine changes and trends in enzyme immobilization research during the past five years. Data were collected from the Web of Science Core Collection database and analyzed using VOSviewer © software. A discussion is presented on the most productive countries, most cited authors, leading publications, main areas of research and industrial applications of immobilized enzymes. China, the USA, India, Brazil and Spain hold the largest numbers of published articles on the topic, and the two main areas of study are chemistry and biotechnology applied microbiology. Trend analysis showed that laccases and lipases were the most commonly used enzymes, whereas nanoparticles and metal–organic frameworks were the most commonly used enzyme supports. The results highlight that immobilization is used to modify several enzyme properties, such as stability, recovery and specificity. Conclusions and future perspectives in the field are also addressed. It is believed that the development of new, low‐cost supports and studies on the scale‐up of processes using immobilized enzymes constitute future research trends. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd